The institutional change from e-government toward smarter city: Comparative analysis between royal borough of Greenwich, UK, and Seongdong-gu, South Korea - Churin Kim; Kyung-ah Kim (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The research questions of the current study include: "Is it beneficial for countries, local governments, and autonomous districts with a high level of e-government to become smarter cities with the electronic, digital, and smart introduction of information and communications technology (ICT) technologies?" "Do cities with well-developed e-governments have a similar process from e-government to smarter cities?", and "Do cities with similar levels of e-government or smarter cities go through different development processes in terms of their socio-cultural attributes?" This study focuses on the fact that e-government and smart cities, whose academic roots arose differently over time, are evolving to address governance, including next-generation e-government, urban e-government, and civic engagement, which has expanded to digital government and platform government concepts. Therefore, the scope of this study is set to e-government and smart/smarter cities as platforms. By comparing the key success factors of e-government with the smart city through a prior study, some intersections were found, but the success factors of the e-government and smart city were different. In order to explain the change of system from e-government to smart city as a platform in the socio-cultural attributes in which each case is involved, two cases-the Royal Borough of Greenwich and Seongdong-gu-were selected under similar conditions by comparing the e-government development level, economic indicators, and smart city development level. As a result of the case analysis, it was confirmed that the development level of e-government affected the smarter city process. The changes in the system from e-government to smart city was capable of being explained in different ways depending on the social and cultural attributes. In the process from e-government to smarter city, the case of Seongdong-gu, which has followed the informatization project and e-government development formula, was analyzed from the viewpoint of institutional overwrap, and the case of the Royal Borough of Greenwich, which was an active innovation agent for solving urban problems through public-private cooperation, was analyzed from the viewpoint of institutional transformation. In the Korean context with a collective hierarchical culture, citizens and stakeholders have participated in the public sector to the extent that they raise issues and express their preferences in policy-making decisions. The governments, including the autonomous district, have still treated citizens and stakeholders as guidance targets or customers rather than cooperative partners. On the other hand, the UK, which has an individualistic rational culture, citizens and stakeholders have become accustomed to maintaining cooperative relationships and operating cities based on partnerships as innovators. Since the socio-cultural contexts of each country have affected the actual system operations and changes, implementation plans and solutions under feasibilities need to take into account critical success factors and the socio-cultural properties of each autonomous district for the introduction, expansion, and establishment of smarter cities. This result of this study is that transferability considering sociocultural properties should be considered when introducing best practices, etc.
Keywords: 650; citizen participation; e-government; institutional changes; smart city; smarter cities